Ligation of high-melting-temperature ‘clamp’ sequence extends the scanning range of rare point-mutational analysis by constant denaturant capillary electrophoresis (CDCE) to most of the human genome - Kim, Andrea S. (Oxford University Press, 2003)
Mutations cause or influence the prevalence of many diseases. In human tissues, somatic point mutations have been observed at fractions at or below 4/10 000 and 5/100 000 in mitochondrial and nuclear DNA, respectively. In human populations, fractions for the multiple alleles that code for recessive deleterious syndromes are not expected to exceed 5 × 10(–4). Both nuclear and mitochondrial point mutations have been measured in human cells and tissues at fractions approaching 10(–6) using constant denaturant capillary electrophoresis (CDCE) coupled with high-fidelity PCR (hifiPCR). However, this approach is only applicable to those target sequences (∼100 bp) juxtaposed with a ‘clamp’, a higher-melting-temperature sequence, in genomic DNA; such naturally clamped targets represent ∼9% of the human genome. To open up most of the human genome to rare point-mutational analysis, a high-efficiency DNA ligation procedure was recently developed so that a clamp could be attached to any target of interest. We coupled this ligation procedure with prior CDCE/hifiPCR and achieved a sensitivity of 2 × 10(–5) in human cells for the first time using an externally attached clamp. At this sensitivity, somatic mutations, each representing an anatomically distinct cluster of cells (turnover unit) derived from a mutant stem cell, may be detected in a series of tissue samples, each containing as many as 5 × 10(4) turnover units. Additionally, rare inherited mutations may be scanned in pooled DNA samples, each derived from as many as 10(5) persons.